2012
DOI: 10.1111/j.1540-8167.2012.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Therapy in Patients with Cardiac Sarcoidosis

Abstract: ICD Shocks in Cardiac Sarcoidosis. Background: An implantable cardioverter defibrillator (ICD)is indicated for some patients with cardiac sarcoidosis (CS) for prevention of sudden death. However, there are little data regarding the event rates of ICD therapies in these patients. We sought to identify the incidence and characteristics of ICD therapies in this patient population.Methods: We performed a cohort study of patients with ICDs at 3 institutions. Cases were those patients with CS and an ICD implanted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 12 publications
6
123
3
2
Order By: Relevance
“…We think that the late observations on the predictive value of myocardial LGE, summarized in Table 5, call for a reevaluation of the recommendation at this point. Importantly, LGE predicted cardiac events despite normal or mildly reduced LV function,11 and in the study by Ise et al12 and in our study, it even outperformed LVEF, the key prognostic factor in CS reported previously 1, 2, 8, 24, 29. It is worth discussing whether some definition of myocardial LGE, for example, extent ≥22% of LV mass or involvement of the RV wall or involvement of ≥9 of 29 combined LV and RV segments (Table 5), should be added as a new or strengthening indication for an ICD in patients with CS and normal or mildly reduced LV function.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We think that the late observations on the predictive value of myocardial LGE, summarized in Table 5, call for a reevaluation of the recommendation at this point. Importantly, LGE predicted cardiac events despite normal or mildly reduced LV function,11 and in the study by Ise et al12 and in our study, it even outperformed LVEF, the key prognostic factor in CS reported previously 1, 2, 8, 24, 29. It is worth discussing whether some definition of myocardial LGE, for example, extent ≥22% of LV mass or involvement of the RV wall or involvement of ≥9 of 29 combined LV and RV segments (Table 5), should be added as a new or strengthening indication for an ICD in patients with CS and normal or mildly reduced LV function.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings support these 2 data sets but also add to the knowledge by identifying impaired RVEF and basal septal thinning as CMRI variables portending poorer outcome. The predictive value of RV function had also been suggested in an earlier study by Schuller et al24 revealing that RV dysfunction, shown by echo, nuclear imaging, or MRI, predicted life‐threatening arrhythmias in CS patients with an ICD. In addition, the data of Crawford et al11 and Blankstein et al25 suggest that life‐threatening arrhythmic events in CS may be related to inflammatory involvement of the RV wall.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…DECMR has become the gold standard test for detecting and quantifying focal myocardial scar, a predictor of high degree atrio‐ventricular block (AVB), heart failure [congestive cardiac failure (CCF)], ventricular tachycardia (VT), and sudden cardiac death (SCD) in CS 2, 3, 4, 5, 6, 7, 8, 10, 11, 12, 13, 14, 15. ( Table 1A and 1B) Systolic right ventricular (RV) impairment and multi‐focal RV late gadolinium enhancement (LGE) on cardiovascular magnetic resonance (CMR) and active RV granulomatous inflammation on PET have been associated with adverse outcomes in retrospective studies 2, 7, 11, 12, 16, 17, 18. We previously demonstrated the diagnostic accuracy of DECMR for CS and reported on RV involvement in pulmonary sarcoidosis utilizing CMR 19, 20.…”
Section: Introductionmentioning
confidence: 99%